Análise da eficiência de unidades de ensino: um comparativo da evolução do desempenho entre os campi do Instituto Federal Farroupilha - Santos, João Pedro Pereira dos (2018)
The availability of Federal Institutes offering technical courses distributed throughout Brazil represents, in a general way, the intention of the government in seeking to resolve the deficiency of the offer of free public education and quality. On the other hand, the implantation of these units in regions with poor infrastructure in aspects such as roads, transportation, among other factors, may indicate the lack of timeliness or the lack of technical planning criteria for the establishment of an expensive structure from which it is expected that demand is greater than supply and that, as a consequence, it will provide positive results for regional development. Therefore, the importance of confronting the current reality in comparison to the period prior to the physical expansion of the Federal Institute Farroupilha (IFFar) can be understood as a procedure of control and follow-up of government actions with a view to assessing how this public policy educational internalization of teaching has carried out its program. The main objective of this work was to analyze the efficiency of the Campus of the Farroupilha Federal Institute based on evolutionary aspects in the period between 2010 and 2016. Theoretical basis was the themes related to economic development; human; sustainable and regional education, as well as benchmarking performance evaluation and efficiency-related aspects, as well as an overview of the Federal Education Network. This work was characterized by being descriptive and quantitative, and used institutional data collection and secondary data provided by statistical research institutes with socioeconomic content related to the region contemplated by the educational institution. The comparative performance analysis was performed among the nine campuses physically established in Rio Grande do Sul. In this case, to reach the main objective, this research sought to perform the performance analysis, if any, already practiced in the educational institution. The following campuses were considered for this purpose: Jaguari; Julio de Castilhos; Saint Vincent; Panambi; Saint pink; Santo Ângelo; Saint Augustine; Alegrete and São Borja. The use of Data Envelopment Analysis (DEA) made it possible to compare the identification and selection of the main variables of inputs and outputs of each campus. The current condition of each campus and its relationship with the socioeconomic development of the region was measured using this methodology, such as the use of free software SIAD v.3.0. Taking into account the period and set of variables selected, the comparative was segmented into three sub periods: 2010 to 2016; 2014 to 2016 and 2015 to 2016, obtaining the result for the Santo Augusto campus as Benchmark with 100% efficiency, followed by the São Borja campus with 97.16% of average efficiency among the campuses in activity from 2010. Although this research has reached the determination of the efficiencies of the units investigated, it is understood that there is still much to adjust to arrive at a more appropriate comparative, considering the time of creation of IFFar. Finally, this work will be proposed as an auxiliary tool for management decision-making in the search for the necessary measures to reach the balance among the teaching units.